1978
DOI: 10.1037/0003-066x.33.3.224
|View full text |Cite
|
Sign up to set email alerts
|

Dangerousness: A paradigm for exploring some issues in law and psychology.

Abstract: The social phenomenon of "dangerousness" is discussed in terms of legal and social responses and in terms of potential contributions by psychology and other behavioral and social sciences toward increased understanding and more effective coping by society with such social problems. Social scientists need to become more concerned with the study of dangerous behaviors and practices in our society, especially in light of the disproportionate injury and harm suffered by socially disadvantaged groups. Although valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(75 citation statements)
references
References 50 publications
1
73
0
1
Order By: Relevance
“…Research indicates that previous criminal behavior is a positive predictor of future criminal behavior (Mossman, 1994;Shah, 1978;Wolfgang, 1978). Further, Mossman (1994) demonstrated that criminal history was a stronger predictor of future criminal behavior than clinical judgments.…”
Section: Definitions Relating To Crime and Criminalitymentioning
confidence: 96%
See 1 more Smart Citation
“…Research indicates that previous criminal behavior is a positive predictor of future criminal behavior (Mossman, 1994;Shah, 1978;Wolfgang, 1978). Further, Mossman (1994) demonstrated that criminal history was a stronger predictor of future criminal behavior than clinical judgments.…”
Section: Definitions Relating To Crime and Criminalitymentioning
confidence: 96%
“…Further, Mossman (1994) demonstrated that criminal history was a stronger predictor of future criminal behavior than clinical judgments. In addition, research suggests that the probability for re-arrest increases with each successive conviction (Shah, 1978;Wolfgang, 1978). Despite this evidence, many researchers have argued that criminal trajectories are not set and that criminal behavior may be discontinued at some point in a criminals' life course (Hollin, 1999;Losel, 1995;Nagin & Paternoster, 1993;Polaschek & Collie, 2004;Sampson & Laub, 2003).…”
Section: Definitions Relating To Crime and Criminalitymentioning
confidence: 97%
“…Son dönemde yapılan araştırmalar, risk faktörleri ve saldırgan davranış arasındaki istatistikî bağlantıyı ortaya koyabilmeye başlamıştır (1). Risk değerlendirmesi, bir kişinin işleyebileceği saldırgan eylemler hakkında spekülasyon yapma ve bu eylemleri önlemek ve olumsuz sonuçlarını en aza indirmektir şeklinde tanımlanmaktadır.…”
Section: Gi̇ri̇ş Ve Amaçunclassified
“…Evidence for this link is, however, contradictory. Psychopathic profiles on the MMPI have been predictive of violence in some studies (e.g., Davis & Sines, 1971), but not others (e.g., Buck & Graham, 1978).A number of authors have commented upon the limitations of the personality model as a predictor of violent behavior (e.g., Shah, 1978). This has led to the notion that traits refer to average behaviors and that predictions of violent behavior would be improved by taking into account the person-situation interaction (e.g., Mischel, 1973).…”
mentioning
confidence: 99%
“…A number of authors have commented upon the limitations of the personality model as a predictor of violent behavior (e.g., Shah, 1978). This has led to the notion that traits refer to average behaviors and that predictions of violent behavior would be improved by taking into account the person-situation interaction (e.g., Mischel, 1973).…”
mentioning
confidence: 99%